LBA6First China-manufactured trastuzumab biosimilar HLX02 global phase III trial met primary endpoint in breast cancer. (24th November 2019) - Xu, B; Zhang, Q; Sun, T; Li, W; Teng, Y; Hu, X; Bondarenko, I; Adamchuk, H; Li, Y; Shan, B; Cheng, J; Peng, T; et al.
Abstract: Background: HLX02, a fully-humanised anti-HER2 monoclonal antibody, was developed as trastuzumab (TZB) biosimilar to potentially increase treatment accessibility. The clinical program was developed in consultation with China National Medical Products Administration (NMPA) and European Medicines Agency (EMA) for global development. Previously, we reported clinical PK equivalence of HLX02 and TZBs at the ESMO-ASIA 2018 meeting. Here, we report the phase III study results. Methods: We conducted a randomised, double-blind, parallel-controlled phase III study of HLX02 and EU-TZB at 89 centres in China, Philippines, Poland and Ukraine. Eligible adult women with HER2+ breast cancer were randomised to 8 mg/kg of either HLX02 or EUTZB with docetaxel on Day 1 Cycle 1 followed by a dose of 6 mg/kg in 3weekly cycles for up to 12 months. Primary endpoint was best overall response rate at Week 24 (ORRwk24 ). Secondary endpoints included ORR at weeks 6, 12, 18 and 24, clinical benefit rate (CBR), disease control rate (DCR), duration of response (DoR), progression-free survival (PFS), overall survival (OS), and safety profiles up to 12 months. Results: Of the 649 patients being randomised (HLX02=324; EUTZB=325), the ORRwk24 (HLX02=71.0%; EU-TZB =71.4%; p = 0.952) and risk difference in ORRs (-0.4%; 95% CI: -7.4, 6.6) between the two groups were within the pre-defined margin (±13.5%). All secondary efficacy analyses at Week 24 concluded the therapeutic equivalence. Both groups in all populations (overall, Asian vs. non-Asian, and Chinese vs. non-Chinese) had similar range values of CBR (HLX02: 78.6% - 86.8%; EU-TZB: 79.3% - 82.4%) and DCR (HLX02: 80.6% - 95.4%; EU-TZB: 86.9% - 89.2%). 641 (98.8%) reported at least 1 AE (HLX02 and EU-TZB were 98.8%). Similar incidences of AEs (HLX02: 6610; EU-TZB: 6788), TEAEs (HLX02: 6464; EU-TZB: 6638) and immunogenicity were reported at Week 24. Conclusions: The use of HLX02 compared with EUTZB resulted in an equivalent ORR at Week 24. All secondary efficacy and safety analyses of HLX02 at Week 24 supported the conclusion of biosimilarity without clinical meaningful differences with EUTZB. This interim analysis has been submitted to NMPA and EMA to support marketing approval of HLX02 in China and Europe. Clinical trial identification: NCT03084237; EudraCT: 2016-000206-10; Chinese Clinical Trial Register: 2015L01326. Legal entity responsible for the study: Shanghai Henlius Biotech, Inc. Funding: Shanghai Henlius Biotech, Inc. Disclosure: T. Sun: Research grant / Funding (institution): Shanghai Henlius Biotech, Inc. W. Li: Research grant / Funding (institution): Shanghai Henlius Biotech, Inc. Y. Teng: Research grant / Funding (institution): Shanghai Henlius Biotech, Inc. I. Bondarenko: Research grant / Funding (institution): Shanghai Henlius Biotech, Inc. H. Adamchuk: Research grant / Funding (institution): Shanghai Henlius Biotech, Inc. Y. Li: Full / Part-time employment: Shanghai Henlius Biotech, Inc. B. Shan: Full / Part-time employment: Shanghai Henlius Biotech, Inc. J. Cheng: Full / Part-time employment: Shanghai Henlius Biotech, Inc. T. Peng: Full / Part-time employment: Shanghai Henlius Biotech, Inc. X. Wang: Full / Part-time employment: Shanghai Henlius Biotech, Inc. Y. Chen: Full / Part-time employment: Shanghai Henlius Biotech, Inc. W. Jiang: Full / Part-time employment: Shanghai Henlius Biotech, Inc. S. Liu: Full / Part-time employment: Shanghai Henlius Biotech, Inc. X. Zhang: Full / Part-time employment: Shanghai Henlius Biotech, Inc. E. Liu: Full / Part-time employment: Shanghai Henlius Biotech, Inc. A. LUK: Full / Part-time employment: Shanghai Henlius Biotech, Inc. Q. Wang: Full / Part-time employment: Shanghai Henlius Biotech, Inc.